2015
DOI: 10.1177/1091581815575757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Pollution-Related Heavy Metals on the Viability and Inflammatory Responses of Human Airway Epithelial Cells

Abstract: Various metals produced from human activity are ubiquitously detected in ambient air. The metals may lead to induction and/or exacerbation of respiratory diseases, but the significant metals and factors contributing to such diseases have not been identified. To compare the effects of each metal and different oxidation states of metals on human airway, we examined the viability and production of interleukin (IL)-6 and IL-8 using BEAS-2B cell line, derived from human airway epithelial cells. Airway epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
(72 reference statements)
2
12
1
Order By: Relevance
“…Ott et al (2004) proposed that a chronic inhalation of Mo may induce subclinical alveolitis. Moreover, Honda et al (2015) concluded that Ni and Zn are also responsible for low cell viability in a certain dose range, which supports our present findings of negative correlations for these two metals as well. An occupational health study established that Co associated with other metals has a respiratory effect as allergic hypersensitivity (Cugell et al 1990).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ott et al (2004) proposed that a chronic inhalation of Mo may induce subclinical alveolitis. Moreover, Honda et al (2015) concluded that Ni and Zn are also responsible for low cell viability in a certain dose range, which supports our present findings of negative correlations for these two metals as well. An occupational health study established that Co associated with other metals has a respiratory effect as allergic hypersensitivity (Cugell et al 1990).…”
Section: Discussionsupporting
confidence: 92%
“…A negative correlation was revealed between some heavy metals and cell viability, and we selected the five most highly correlated metals for a discussion of their cytotoxicity: Mn, Mo, Zn, Co and Ni (Table 1). Previous study Honda et al (2015) showed that TC50 values (concentration that reduces cell viability to 50%) of Mn +2 in airway epithelial cells were as low as 3.0µM. Mn has a proven neurological effect and also increased the risk of lung cancer (Mirmohammadi 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated dose-dependent immunomodulatory effects of Pb 17 , 18) , and human studies have found that occupational lead exposure is associated with altered levels of certain pro-inflammatory cytokines, although the majority of studies focus only on chronic lead exposure. Valentino et al 6) reported higher plasma TNF-α in workers chronically exposed to Pb (BLL = 9.1-46.0 μg/d l ) compared to non-exposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cutting, and the grinding and drilling of mild steel all create a significant amount of respirable particulate, with 42% of particulate generated below 2 µm, and grinding and drilling producing a full third and 20% below 1 µm, respectively [30,31]. This presents a challenge, as plasma table operators are likely to have a similar amount of exposures as other beamline operators, and yet are exposed to the oxides of metal, rather than elemental metal, and oxidation states do affect toxicodynamics [32,33]. In practice, the Alberta Occupational Health and Safety Code does not distinguish between elemental and oxides of iron or manganese [27] which makes mechanically and thermally generated metal exposure comparable, and allows plasma drill and beamline operators to belong to the same SEG.…”
Section: Discussionmentioning
confidence: 99%